Implementasi Metode Simulasi Ekskavasi pada Pembelajaran Sejarah dalam Menumbuhkan Kemampuan Berpikir Historis Siswa Kelas X SMAN 1 Kabupaten Tangerang - Nabila Agustin; Rikza Fauzan; Eko Robawati (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
History instruction in senior high schools often relies on lectures and memorization, resulting in limited development of students’ historical thinking skills. This study examines the planning, implementation, and impact of excavation simulation on the historical thinking skills of tenth-grade students at SMAN 1 Kabupaten Tangerang. A qualitative case study approach was applied, supported by a Likert-scale questionnaire involving 112 students from two experimental classes and one control class. Data were collected through observations, interviews with teachers and students, and document analysis, then analyzed using the Miles and Huberman interactive model with source and method triangulation. The results indicate that excavation simulation was designed through several stages, including module preparation and replica artifact selection, although equipment availability remained dependent on teacher initiative. The implementation involved material explanation, group activities, excavation processes, documentation of findings, and report preparation. Students showed high enthusiasm despite limited facilities and weather constraints. The experimental classes achieved higher average scores (4.12–4.25) than the control class (3.10), particularly in the sourcing dimension. Excavation simulation supports historical thinking through sourcing, contextualization, and corroboration, making it an effective contextual learning method aligned with the Merdeka Curriculum.